Isolation and Immunosuppressive Effects of 6″-O-Acetylginsenoside Rb1 Extracted from North American Ginseng - Samimi, Raziye; Xu, William Z.; Lui, Edmund M. K.; Charpentier, Paul A. (Planta Medica, 2014)
Extraction of medicinally active components from natural health products has become an emerging source for drug discovery. Of particular interest for this work was the finding and testing of a new ginsenoside from North American ginseng (Panax quinquefolius). In the present study, a large amount of 6″-O-acetylginsenoside Rb1, compound 7, was found using ultrasonic extraction of North American ginseng with DMSO aqueous solution. This new ginsenoside was well identified with MS, FTIR, and 1D (1H and 13C) and 2D (gCOSY, gHSQC, and gHMBC) NMR. Subsequent bioassay experiments confirmed that compound 7 demonstrated an additional immunosuppressive activity towards inhibiting the production of nitric oxide and tumor necrosis factor alpha in lipopolysaccharide-induced macrophage cells in a dose-dependent manner using murine macrophages. This new ginsenoside is encouraging for the further exploration and development of novel drugs.
Keywords: Panax quinquefolius; Araliaceae; DMSO; immunosuppressive; 6″-O-acetylginsenoside Rb1; saponin